A survey on energy-efficient clustering techniques and mobile-agent based data aggregation techniques in WSN - Pathak, Nishant Kumar; Sidhu, Harmaninderjit Singh (International Journal of Psychosocial Rehabilitation, 2020)
Data aggregation is one of Wireless Sensor Networks (WSN) popular techniques in reducing data duplication and increasing the energy efficiency. Sensor node energy constraints include methods of energy intensive data compression in order to extend the lifespan of the network. Among the different methods proposed to improve the efficiency of data aggregation were clustering and mobile agents in WSN. This paper presents a systematic review of the energy-efficient clustering schemes and mobile agent-based schemes used by the data aggregation protocols in WSN. The survey will then present a comparative analysis of clustering schemes and mobile agent-based schemes with a focus on their goals along with their strengths and limitations. This survey facilitates the researchers to select the appropriate clustering schemes and mobile agent based schemes employed by protocols for energy-efficient data aggregation in WSN.